2022
DOI: 10.3390/diagnostics12040806
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Echocardiography Assessment of Right Ventricular Volumes and Function: Technological Perspective and Clinical Application

Abstract: Right ventricular (RV) function has important prognostic value in a variety of cardiovascular diseases. Due to complex anatomy and mode of contractility, conventional two-dimensional echocardiography does not provide sufficient and accurate RV function assessment. Currently, three-dimensional echocardiography (3DE) allows for an excellent and reproducible assessment of RV function owing to overcoming these limitations of traditional echocardiography. This review focused on 3DE and discussed the following point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 114 publications
0
1
0
Order By: Relevance
“…Eventually, due to RV structural complexity, 3D echocardiography is currently used as an accurate and reliable method for RV function evaluation compared to above 2D based methods. Studies showed strong correlation between 3D echocardiography and CMR RV volume and function [9].…”
Section: Rv Functionmentioning
confidence: 96%
“…Eventually, due to RV structural complexity, 3D echocardiography is currently used as an accurate and reliable method for RV function evaluation compared to above 2D based methods. Studies showed strong correlation between 3D echocardiography and CMR RV volume and function [9].…”
Section: Rv Functionmentioning
confidence: 96%
“…This intricate process is instigated by the heightened afterload imposed on the RV, ultimately culminating in the manifestation of right heart failure and consequential mortality ( 3 ). Prior investigations have substantiated the pivotal role of RV function as a significant prognostic determinant in patients afflicted by PH, irrespective of the diverse etiological factors underlying the condition ( 4 ). Given the continuous nature of the circulatory system and the holistic nature of the left and right ventricles, which are determined by the presence of a shared septum and pericardial constraints, the interdependence of the RV and left ventricles (LV) is a factor that requires consideration ( 5 ).…”
Section: Introductionmentioning
confidence: 99%